(untitled) - Gear, Jolene; Jolene Gear; Robert Gear (Cambridge, UK,New York. N.Y., USA, 2002)
This comprehensive test preparation course includes skill building and practice tests all in one volume to help learners succeed on the Test of English as a Foreign Language. Fully revised and updated, the third edition of Cambridge Preparation for the TOEFL Test provides a complete tutorial and wealth of new activities to introduce students to the new computer formats and activity types. The third edition also includes a CD-ROM component containing seven complete practice tests. Learners may take the tests in study mode and receiving feedback on their responses, or in test mode, which simulates the experience of taking the exam by computer.
Keywords: Test of English as a Foreign Language